Design and preparation of ultra-high performance concrete with low environmental impact. (20th March 2019) - Shi, Ye; Long, Guangcheng; Ma, Cong; Xie, Youjun; He, Jionghuang
Abstract: Ultra-high performance concrete (UHPC) is one of the most promising materials to reduce the detrimental effects of building materials on the environment because UHPC requires fewer materials and post-maintenance in comparison with normal concrete. However, the high cost and CO2 emission of UHPC are the major factors influencing its large-scale application in China. This study presents a series of comprehensive methods, including the optimization design of the binder system, utilization of nano-particles and chemical activators as well as heat curing, to prepare UHPC with relatively lower environmental impact. The workability, compressive strength, flexural strength, hydration heat and environmental impact of UHPC were investigated. The results indicate that each of the above methods has a significant effect on the strength and carbon emission of UHPC. UHPC with cement content lower than 200 kg/m 3 can be prepared by optimizing its binder system and curing conditions, and its embodied CO2 index is lower than 3 kg/MPa·m 3, while the embodied CO2 index of conventional UHPC ranges from 5.5 to 7 kg/MPa·m 3 . The designed UHPC has a low hydration release heat which may decrease the cracking risk caused by hydration temperature rise. For improving the mechanical strength and the eco-friendliness of UHPC, chemical activating method and heat curing have a synergistic effect. Highlights: The low carbon emission UHPC has been successfully prepared in this study. The effect of compositions and curing regime on environmental impact of UHPC were studied. The effect of nano-silica and chemical activators on environmental impact of UHPC were studied. The environmental impact of the optimized and normal UHPC is compared.